Plant volatiles induced by herbivore egg deposition affect insects of different trophic levels. - Nina E Fatouros; Dani Lucas-Barbosa; Berhane T Weldegergis; Foteini G Pashalidou; Joop J A van Loon; Marcel Dicke; Jeffrey A Harvey; Rieta Gols; Martinus E Huigens (PLoS ONE, 2012)
Plants release volatiles induced by herbivore feeding that may affect the diversity and composition of plant-associated arthropod communities. However, the specificity and role of plant volatiles induced during the early phase of attack, i.e. egg deposition by herbivorous insects, and their consequences on insects of different trophic levels remain poorly explored. In olfactometer and wind tunnel set-ups, we investigated behavioural responses of a specialist cabbage butterfly (Pieris brassicae) and two of its parasitic wasps (Trichogramma brassicae and Cotesia glomerata) to volatiles of a wild crucifer (Brassica nigra) induced by oviposition of the specialist butterfly and an additional generalist moth (Mamestra brassicae). Gravid butterflies were repelled by volatiles from plants induced by cabbage white butterfly eggs, probably as a means of avoiding competition, whereas both parasitic wasp species were attracted. In contrast, volatiles from plants induced by eggs of the generalist moth did neither repel nor attract any of the tested community members. Analysis of the plant's volatile metabolomic profile by gas chromatography-mass spectrometry and the structure of the plant-egg interface by scanning electron microscopy confirmed that the plant responds differently to egg deposition by the two lepidopteran species. Our findings imply that prior to actual feeding damage, egg deposition can induce specific plant responses that significantly influence various members of higher trophic levels.